2007
DOI: 10.2203/dose-response.07-004.mattson
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint: Mechanisms of Action and Therapeutic Potential of Neurohormetic Phytochemicals

Abstract: ᮀ The nervous system is of fundamental importance in the adaptive (hormesis) responses of organisms to all types of stress, including environmental "toxins". Phytochemicals present in vegetables and fruits are believed to reduce the risk of several major diseases including cardiovascular disease, cancers and neurodegenerative disorders. Although antioxidant properties have been suggested as the basis of health benefits of phytochemicals, emerging findings suggest a quite different mechanism of action. Many phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 79 publications
1
93
0
1
Order By: Relevance
“…Taken together these findings indicate the dose dependent dimorphic actions of Bardoxolone methyl analogs on CKD progression with favorable effect at a low drug dosage and toxic effects at a high dosage. The dimorphic response to the Bardoxolone analogs which are potent synthetic Nrf2 inducers is consistent with the well-known hormetic properties of the natural plantbased Nrf2 activators [37,38]. These phytochemicals found in fruits and vegetables are known to reduce the risk of cancers, neurodegenerative disorders, and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 73%
“…Taken together these findings indicate the dose dependent dimorphic actions of Bardoxolone methyl analogs on CKD progression with favorable effect at a low drug dosage and toxic effects at a high dosage. The dimorphic response to the Bardoxolone analogs which are potent synthetic Nrf2 inducers is consistent with the well-known hormetic properties of the natural plantbased Nrf2 activators [37,38]. These phytochemicals found in fruits and vegetables are known to reduce the risk of cancers, neurodegenerative disorders, and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 73%
“…SF has been used as a chemopreventive compound (19). The cytoprotective effect of SF is explained mainly by activation of the Nrf2-ARE pathway (20). In vivo studies have shown that SF protects the brain against hypoxicSulforaphane protects against 6-hydroxydopamine-induced cytotoxicity by increasing expression of heme oxygenase-1 in a PI3K/Akt-dependent manner ischemic injury through induction of Nrf2-dependent phase 2 enzyme (21).…”
Section: Introductionmentioning
confidence: 99%
“…Plants use the array of phytochemicals that serve multiple purposes, for example: protection from abiotic stress, like excessive UV radiation (polyphenols, terpenes and terpenoids), attraction of pollinators (volatile terpenes), warding off herbivores (noxious phytochemicals, e.g. alkaloids), protection from bacterial or fungal infections (polyphenols, terpenoids, etc) [1][2][3][4]. Herbivores evolved different forms of biochemical changes, that protect them from the deleterious effects of some of the phytochemicals, for example: CYP450 superfamily of enzymes, transporter proteins and stress-response cellular signalling pathways [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…alkaloids), protection from bacterial or fungal infections (polyphenols, terpenoids, etc) [1][2][3][4]. Herbivores evolved different forms of biochemical changes, that protect them from the deleterious effects of some of the phytochemicals, for example: CYP450 superfamily of enzymes, transporter proteins and stress-response cellular signalling pathways [1][2][3][4]. Many of these mechanisms are highly conserved adaptive stress response systems that humans share with simple herbivores.…”
Section: Introductionmentioning
confidence: 99%